Evolution of population structure in a commercial European hybrid dent maize breeding program and consequences on genetic diversity - Romain Kadoumi; Nicolas Heslot; Fabienne Henriot; Alain Murigneux; Mathilde Berton; Laurence Moreau; Alain Charcosset (Theoretical and Applied Genetics, 2025)
Key message Differentiation between Stiff Stalk and Non-Stiff Stalk heterotic groups increased significantly over time, while genetic diversity within both groups declined, highlighting the impact of long-term selection in hybrid maize breeding. Abstract Differentiation between Stiff Stalk and Non-Stiff Stalk heterotic groups increased significantly over time, while genetic diversity within both groups declined, highlighting the impact of long-term selection in hybrid maize breeding. The separation of germplasm into complementary heterotic genetic pools is fundamental to modern hybrid breeding programs. This approach facilitates the development of high-performing hybrids by maximizing heterosis through crosses of divergent inbred lines. Maintaining heterotic structure ensures continuous genetic gain and selection of divergent alleles, but introducing novel germplasm is equally important to mitigate the risks of diversity loss from repeated selection of elite material. This study presents a large-scale assessment of the evolution of genetic diversity, population structure, and differentiation between heterotic groups, within a private European hybrid dent maize breeding program. Forty years of breeding data and 84,000 genotypes were used. Clustering methods revealed two main heterotic groups in modern germplasm: Stiff Stalks and Non-Stiff Stalks. These two groups originated from Stiff Stalk, Iodent, and Lancaster founders, forming three ancestral groups. Differentiation between heterotic groups was low for early founder inbreds and increased over time. Consistently, intragroup diversity decreased over time, and marker fixation and linkage disequilibrium increased. The main cause of diversity loss germplasm-wide was the merging and genetic homogenization of the ancestral Iodent and Lancaster groups into the modern Non-Stiff Stalk heterotic group. Insights into the genetic relationship between hybrid heterotic group population structure and intragroup diversity can assist breeders in enhancing heterotic group divergence, while preserving diversity across selection cycles. This study provides an overview of the evolution of key genetic metrics, to inform strategies for managing diversity and differentiation in commercial hybrid breeding programs.

Ten novel mutations in the molybdenum cofactor genes MOCS1 and MOCS2 and in vitro characterization of a MOCS2 mutation that abolishes the binding ability of molybdopterin synthase - Silke Leimkühler; Mathilde Charcosset; Philippe Latour; Claude Dorche; Soledad Kleppe; Fernando Scaglia; Irmina Szymczak; Petra Schupp; Rita Hahnewald; Jochen Reiss (Human Genetics, 2005)